2x^2 + 14x = -12
Step 1: Subtract -12 from both sides.
2x^2 + 14x - (-12) = -12 - (-12)
2x^2 + 14x + 12 = 0
Step 2: Factor the left side of the equation.
2(x + 1)(x + 6) = 0
Step 3: Set Factors equal to 0.
x + 1 = 0 or x + 6 = 0
x = -1 or x = -6
Answer:
x = -1 or x = -6
Hope this helps. : )
Answer:
42p + 21r
Step-by-step explanation:
First look at the parentheses. Since 4p and 2p are the same variables, you can add them.
7(6p + 3r)
now you use the distributive property.
7 x 6p + 7 x 3r
42p + 21r
and then you get you’re answer.
This is how you would graph y=5x+1
Answer:
Order from Least to Greatest
1/8 < 1/6 < 1/4 < 1/3 < 2/5 < 3/5 < 2/3
Step-by-step explanation: